2013
DOI: 10.1007/s12031-013-0083-8
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Salvianolic Acid B on Blood–Spinal Cord Barrier After Compression Spinal Cord Injury in Rats

Abstract: Salvianolic acid B (Sal B), a bioactive compound isolated from the Chinese medicinal herb danshen, is commonly used for the prevention and treatment of cardiovascular disease. The present study was performed to investigate the effect of Sal B on the blood-spinal cord barrier (BSCB) after spinal cord injury (SCI) in a rat model. Sal B (1, 10, and 50 mg/kg i.v.) was administered to rats immediately following SCI. The permeability of the BSCB and spinal cord tissue water content were evaluated. Additionally, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…This could have an important impact on clinical translational efforts, given that the lack of biomarkers to detect therapeutic effects is an important gap in the field that could be bridged by this technology. 32,33 In addition, given sufficient exposure of the lesioned spinal cord after decompressive laminectomy, peri-and intraoperative VHRUS has the potential to enhance the accuracy of prognosis of SCI by enabling a fast, safe, and accurate visualization of the severity and extent of the vascular lesion. It can also theoretically improve the accuracy of targeted stereotactic cell injections and minimize damage to spared tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This could have an important impact on clinical translational efforts, given that the lack of biomarkers to detect therapeutic effects is an important gap in the field that could be bridged by this technology. 32,33 In addition, given sufficient exposure of the lesioned spinal cord after decompressive laminectomy, peri-and intraoperative VHRUS has the potential to enhance the accuracy of prognosis of SCI by enabling a fast, safe, and accurate visualization of the severity and extent of the vascular lesion. It can also theoretically improve the accuracy of targeted stereotactic cell injections and minimize damage to spared tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that multiple herbs and herbal extracts of Traditional Chinese Medicine (TCM) are effective in the treatment of central nervous system diseases such as Parkinson's disease (Hong et al, 2014), Alzheimer disease (Rafii et al, 2011) and spinal cord injury (Fan et al, 2013). Rhodiola is a widely used TCM herb that has been shown to improve cognitive function, reduce mental fatigue, decrease free radicals, and enhance learning and memory (Darbinyan et al, 2000;Shevtsov et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a severe trauma of the central nervous system (CNS) that results in loss of blood vessels and disruption of the blood-spinal cord barrier (BSCB) (1,2). Previous studies focused largely on alleviating neurological manifestations of the injury while ignoring pathological changes in the spinal cord (3).…”
Section: Introductionmentioning
confidence: 99%